Full-Scale Experimental Study on Influence of Smoke on Pedestrian Movement During Evacuation in Road Tunnel - Natalia Schmidt-Polończyk (Buildings)
The article presents the results of experimental studies of evacuation of 50 people from a road tunnel in various smoke conditions. Calculations of total evacuation times, pre-movement times and movement speeds were carried out and the impact of smoke on the speed of movement was analyzed. The pre-movement times, the alarm realization and response times for the subsequent experiments (1, 2 and 3) were 36, 7 and 5 s, respectively. The total evacuation times for 3 experiments were 340, 301 and 215 s. It has been shown that the speed of movement in smoke depends not only on the density of smoke, but also on the very attitude of the experiment participants and knowledge of the tunnel. It has also been shown that the adverse impact of low visibility on the evacuation time and movement speed is as important as the motivation of the evacuees and the effect of learning. In order to collect the observations of the participants, as well as assess potential aspects which might have influenced the process of evacuation, a survey was conducted after both experiments. The answers show that the two main reasons that prompted the evacuation were smoke in the tunnel and the fire drill.